The Development of UMS Building Catalogue Information System - Ganno Tribuana Kurniaji; Mohammad Faqih Eza 'Ammar; Yusuf Sulistyo Nugroho (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2022)
Universitas Muhammadiyah Surakarta (UMS) as one of the biggest private university in Indonesia has a large number of new students per year. However, most new students often get confused to identify and even do not know the location of the buildings that handle various activities in the early period of lectures, such as student orientation, English pre-tests, etc. This is due to lack of information provided by the university to the new enrolled students. To overcome this problem, this work aims to develop a web-based building catalogue by implementing a framework, namely Ionic. This system is built to help the new students getting the building-related information in UMS and find out the location of the building. By following the waterfall model to build the system, the results show that we have successfully developed the building catalogue information system. The main page of the information system displays a list of buildings that are within the scope of UMS, starting from Building A to Building L completed with photos and detailed information about the building. The system is helpful for new students to get the information of all buildings in UMS.